Physicochemical characterization of natural dolomite for efficient removal of lead and cadmium in aqueous systems. Issue 6 (4th May 2018) - Sdiri, Ali
Abstract : Physicochemical characterization of naturally abundant carbonates has been undertaken to evaluate their potentialities in the removal of lead and cadmium ions in aqueous systems. Powdered dolomite samples, collected from the Jebel Rehach location, southern Tunisia, were used in their natural form for the removal of both cadmium and lead in aqueous conditions. The removal experiments were carried out in batch by mixing known amount of dolomite powder with a metal solution (lead or cadmium). The mixture was shaken at 200 rpm under the experimental conditions of pH 6, temperature (25°C), dolomite concentration 3 g/L, and cadmium 10 mg/L and lead 100 mg/L solutions. Shaking time was 60 min. Our results showed that the studied dolomite samples were mainly composed of calcium and magnesium oxides; other impurities were also detected. Adsorption data showed that dolomitic samples of the Triassic Rehach formation (southern Tunisia) removed substantial amounts of lead and cadmium ions in aqueous systems. It was found that lead removal efficiency reached 24.80 and 33.25 mg/g, which is much higher than that of cadmium (1.31–1.77 mg/g). It was also observed that more than 95% of the total adsorptive capacity was achieved after 30 min of agitation, but 60 min was used to ensure equilibration time. These results suggested that the Triassic Rehach dolomite, Tunisia, can be effectively used for capturing lead and cadmium ions in aqueous conditions. © 2018 American Institute of Chemical Engineers Environ Prog, 37: 1901–1907, 2018